A new score for the diagnosis of complicated appendicitis in children - Complicated appendicitis pediatric score - Adelais K Tzortzopoulou; Mariza Tsolia; Nicolaos Spyridis; Panagiota Giamarelou; Rodanthi Sfakiotaki; Alexander Passalides; Nicolaos Zavras (Wolters Kluwer Medknow Publications, 2022)
Aim: This study aims to construct and validate a new score for diagnosis of complicated appendicitis in children, complicated appendicitis pediatric score (CoAPS), to guide residents' clinical decision-making on choosing the correct patients for immediate surgery, reducing the emergency negative surgeries. Methods: This prospective observational study enrolled two cohorts of patients 5-15 years old. Four hundred and seven consecutive patients were enrolled for the derivation cohort. Demographic data, clinical features, and histopathology data were collected. The outcome measure was the histological diagnosis of gangrenous appendicitis with or without perforation. The score was next validated in a separate cohort of 312 consecutive patients who were classified according to their risk of complicated appendicitis. The diagnostic performance of the score and the potential for the risk stratification to select patients for diagnostic imaging, emergency operative management, and reduce emergency negative operation rates were quantified. Results: A positive "jumping up" test, vomiting, white blood cell >13.5 × 10^3/ml, lymphocytes <18%, and C-reactive protein >50 mg/dl were independent predictors for complicated appendicitis. The final prediction model exhibited an area under the curve of 0.890 (95% confidence interval: 0.859-0.922). The low-risk group demonstrated high sensitivity (90.4%) for complicated appendicitis, while scores 6 or more were very specific (95%) for the disorder. Describing the potential utility of the score, emergency ultrasound imaging would have been postponed in 14.5% of patients (P = 0.0016), and emergency negative explorations would have been cut by 87%. Conclusion: The CoAPS score could guide residents in emergency management of children with complicated appendicitis reducing hospitalizations and urgent surgeries.